Characterization of the effect of an epoxy adhesive in hybrid FSW-bonding aluminium-steel joints for naval application. (December 2020) - Maggiore, Sofia; Pedemonte, Matteo; Bazurro, Alessio; Stagnaro, Paola; Utzeri, Roberto; Luciano, Giorgio
Abstract: This study focused on the characterization of an epoxy resin-based adhesive used in the hybrid friction stir welding-adhesive bonding (FSW-AB) technology which involves the use of polymeric adhesives to join aluminium and steel elements giving significant advantages as well as uniform distribution of bond-joint stress, protection from corrosion, and reduced noise and vibration. Thermo-analytical techniques such as differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) were applied to study the curing rate of the structural epoxy adhesive. Infrared (IR) spectroscopy was used to examine the material before and after cure, scanning electron microscopy (SEM) to perform for the morphological analysis and microcalorimetry to evaluate the fire resistance properties. The mechanical performance of metal joints bonded by epoxy resin were studied as well. The joint strength was determined by utilizing single-lap shear test. The experimental results showed that single lap joints (SLJs) in the presence of the epoxy adhesive increased shear strength compared to SLJs of neat metals.